v(x)=(12-2x)(16-2x)(x)

Simple and best practice solution for v(x)=(12-2x)(16-2x)(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for v(x)=(12-2x)(16-2x)(x) equation:


Simplifying
v(x) = (12 + -2x)(16 + -2x)(x)

Multiply v * x
vx = (12 + -2x)(16 + -2x)(x)

Reorder the terms for easier multiplication:
vx = x(12 + -2x)(16 + -2x)

Multiply (12 + -2x) * (16 + -2x)
vx = x(12(16 + -2x) + -2x * (16 + -2x))
vx = x((16 * 12 + -2x * 12) + -2x * (16 + -2x))
vx = x((192 + -24x) + -2x * (16 + -2x))
vx = x(192 + -24x + (16 * -2x + -2x * -2x))
vx = x(192 + -24x + (-32x + 4x2))

Combine like terms: -24x + -32x = -56x
vx = x(192 + -56x + 4x2)
vx = (192 * x + -56x * x + 4x2 * x)
vx = (192x + -56x2 + 4x3)

Solving
vx = 192x + -56x2 + 4x3

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Divide each side by 'x'.
v = 192 + -56x + 4x2

Simplifying
v = 192 + -56x + 4x2

See similar equations:

| 10k-11k=20 | | 0x+2y+2z=0 | | -2x+x-5=3x+3 | | k(x)=3(x-1)(x+1) | | 1.06(1.26)(7-x)=8 | | -3r+7-7=13-7 | | 1.06(1.26)77-x=8 | | (2x^2)+2+14x=90 | | y=2+13y | | 20x+y=180 | | 12x+6x^2=9x^2 | | 2(5x+3)=x+6(x+1) | | 7y+3x=58 | | -3/7(2)-2=y | | 7+63y= | | 6p-8p+-5=-17 | | 55m+5= | | 7x+4+5x+3+2+5=180 | | .80(5-20x)=-44 | | (-3)^5/(-3)^8 | | 102=-3(6n-4) | | h(x)=(2x+5)(3x-1) | | 7^5/7^3 | | (-4)^8/(-4)^4 | | 8^4/8^0 | | -6x^2+11-13=0 | | (-3)^6/(-3)^8 | | (-8w+8)-(w-2)= | | 8cosx=6 | | -6w-(-4z+5w)+7z= | | 78x+31=90 | | 78x+31=180 |

Equations solver categories